An Unusual Fullerene–Carbene Adduct: Thermal Motion, Disorder, or Both?. Issue 2 (16th January 2023) - Carreras, Abel; Lorbach, Andreas; Bazan, Guillermo C.; Alemany, Pere; Wu, Guang; Garcia‐Garibay, Miguel A.; Maverick, Emily F.
Abstract: A single‐crystal X‐ray study of a fullerene‐imidazole adduct at nine temperatures (80 K≤ T ≤480 K), accompanied by energy calculations, strongly suggested thermal motion of the C60 moiety with respect to the imidazolium heterocycle. Analysis of the anisotropic displacement parameters, calculations of frequencies, and the refinement of disorder models for the crystal at four temperatures (230 K≤ T ≤380 K) lead to the conclusion that the rotator is moving at all temperatures. The rotation barrier is low, with one preferred crystallographic site and several other energy minima. Abstract :